Infected non-union of sub-trochanteric fracture of femur treated by Ilizarov and AO external fixation: a case report - Ponugoti, Godhasiri; Shah, Harshad Mohanlal; Reddy, Sandeep; Murthy Vishal, Navale Venkatesh (International Journal of Research in Orthopaedics, 2019)
Infected non-union of fractures of the shaft of proximal femur in paediatric age group is rare. They pose a formidable challenge to the treating orthopaedic surgeon. Concomitant infections elsewhere in the body are a risk factor for infection of fractures treated by open reduction. In our patient the infected non-union was secondary to urinary tract infection. A 12 year old boy sustained an open pelvic injury with bladder rupture and left closed sub-trochanteric fracture. Open reduction and internal fixation (ORIF) was done initially which got infected due to concomitant urinary tract infection due to bladder injury. He was treated by Ilizarov external fixation and later by AO external fixator and the functional outcome is evaluated. This patient had to undergo multiple surgeries with external fixations to control infection & achieve union which took a long period of 8 months. Primary external fixators in complicated cases and in cases prone for infection reduce the need for multiple surgeries.